The Hidden theological and philosophical presuppositions motivating the modern cosmological discussion: Why both sides are wrong - Taylor, Michael Dominic (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2020)
Book review: David Alcalde, Cosmology Without God?: The Problematic Theology Inherent in Modern Cosmology, Cascade, Eugene 2019, pp.226.
Keywords: cosmology; metaphysics; extrincisim; theology; God